An efficient chemoenzymatic synthesis of the bactericide lapyrium chloride - Rustoy, Eduardo Miguel (2005)
An efficient route for large-scale preparation of lapyrium chloride, a broad-spectrum antimicrobial surfactant, was developed from chloroacetic acid in four steps, three of them enzymatic. Due to the chemoselective behavior of the biocatalysts, lapyrium chloride was obtained in a high degree of purity and yield, from mild reaction conditions and following a low environmental impact methodology.